2022
DOI: 10.1002/cyto.a.24677
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of Pfizer‐BioNTech COVID‐19 vaccinations on platelets

Abstract: There is a global concern about the safety of COVID‐19 vaccines associated with platelet function. However, their long‐term effects on overall platelet activity remain poorly understood. Here we address this problem by image‐based single‐cell profiling and temporal monitoring of circulating platelet aggregates in the blood of healthy human subjects, before and after they received multiple Pfizer‐BioNTech (BNT162b2) vaccine doses over a time span of nearly 1 year. Results show no significant or persisting plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…The expression of platelet activation markers –P-selectin, activated GpIIbIIIa, TF, platelet-granulocyte and platelet-monocyte aggregate formation, total and TF-positive MV formation- was analyzed by flow cytometry on whole blood samples, thus in the absence of any pre-analytical manipulation. Results showed the absence of any change in the classical platelet activation parameters following vaccination, confirming previous data [19] , [20] , [21] , [22] . Interestingly a mild, although statistically significant, increase in platelet TF-dependent prothrombotic potential was observed only in ChAdOx1-S Vaxzevria immunized subjects.…”
Section: Discussionsupporting
confidence: 89%
“…The expression of platelet activation markers –P-selectin, activated GpIIbIIIa, TF, platelet-granulocyte and platelet-monocyte aggregate formation, total and TF-positive MV formation- was analyzed by flow cytometry on whole blood samples, thus in the absence of any pre-analytical manipulation. Results showed the absence of any change in the classical platelet activation parameters following vaccination, confirming previous data [19] , [20] , [21] , [22] . Interestingly a mild, although statistically significant, increase in platelet TF-dependent prothrombotic potential was observed only in ChAdOx1-S Vaxzevria immunized subjects.…”
Section: Discussionsupporting
confidence: 89%
“…Thrombosis, platelet aggregation, platelet activity, embolism, and thrombocytopenia have been investigated in healthy individuals vaccinated with adenoviral or mRNA vaccines. Several studies have reported that no vaccine-induced side effects such as persistent platelet aggregation, activation, or plasma thrombin generation have been observed in healthy individuals after COVID-19 vaccination in the long or short term ( 17 19 ). On the contrary, viral vector and mRNA COVID-19 vaccines might cause mild-to-severe adverse health effects in people with blood disorders, according to the literature.…”
Section: Covid-19 Vaccine-induced Thrombotic Eventsmentioning
confidence: 99%
“…In the same study, reduced ADAMTS13 as well as elevated vWF: Ag levels mean that the vWF: Ag/ADAMTS13 ratio dramatically increased in patients recovered from COVID-19 ( 107 ). Studies indicated that markers of platelet activation returned to normal at 2-3 months post-discharge ( 147 , 148 ). Notably, circulating NETs biomarkers reverted towards normal levels around 4 months following infection compared to healthy controls ( 149 , 150 ).…”
Section: Endothelial Activation and Coagulation Abnormalitiesmentioning
confidence: 99%